(untitled) (Asian Journal of Medical and Biological Research, 2016)
Four edible mushroom species (Pleurotus ostreatus, Agaricus bisporus, Volvariella volvacea, Ganoderma lucidum) from different locations of Bangladesh, were analysed for their protein and metal content profile (K, Na, Fe, Cu, Zn, Mn, Cr, Pb, As and Cd). Trace metals were determined by atomic absorption spectrophotometer, Na and K by flame emission spectrophotometer and protein by micro Kjeldhal method. All element concentrations were determined on a dry weight basis. The protein content of mushrooms varied from 13.8%34.3% and the metal content of samples ranged from 0.542.25% for K and 12.681.6, 69.5626.2, 39.2163.4, 30.175.5, 52.9104.5, 0.200.30, 0.130.59 ?g g-1 for Na, Fe, Cu, Zn, Mn, Cd, Pb, respectively. Arsenic and cadmium concentrations were below the detection limit of the method used. The detection limits of the method for As and Cd are 0.01 ?g g-1 for each element. In general, K and Fe content were higher than other metals in all mushroom species. The levels of Cu and Zn in some mushroom samples were found to be higher than legal limits. Asian J. Med. Biol. Res. December 2015, 1(3): 495-501